Determination of the spectrum of low molecular mass organic acids in urine by capillary electrophoresis with contactless conductivity and ultraviolet photometric detection--an efficient tool for monitoring of inborn metabolic disorders - Tůma, Petr; Samcová, Eva; Stulík, Karel (Analytica chimica acta, 2011)
A mixture of 29 organic acids (OAs) occurring in urine was analyzed by capillary electrophoresis (CE) with capacitively coupled contactless conductivity detection (C(4)D) and UV photometric detection. The optimized analytical system involved a 100 cm long polyacrylamide-coated capillary (50 μm i.d.) and the background electrolyte of 20mM 2-morpholinoethanesulfonic acid (MES)/NaOH+10% (v/v) methanol, pH 6.0 (pH is related to the 20mM MES/NaOH buffer in water). The LOD values obtained by C(4)D for the OAs which do not absorb UV radiation range from 0.6 μM (oxalic acid) to 6.8 μM (pyruvic acid); those obtained by UV photometry for the remaining OAs range from 2.9 μM (5-hydroxy-3-indoleacetic acid) to 10.2 μM (uric acid). The repeatability of the procedure developed is characterized by the coefficients of variation, which vary between 0.3% (tartaric acid) and 0.6% (5-hydroxy-3-indoleacetic acid) for the migration time and between 1.3% (tartaric acid) and 3.5% (lactic acid) for the peak area. The procedure permitted quantitation of 20 OAs in a real urine sample and was applied to monitoring of the occurrence of the inborn metabolic fault of methylmalonic aciduria.
Keywords: Young Adult; Urinalysis; vrozené poruchy metabolismu aminokyselin; elektroforéza kapilární; Electric Conductivity; mladý dospělý; Organic Chemicals; kyseliny; Adult; analýza moči; dospělí; organické látky; Amino Acid Metabolism, Inborn Errors; reprodukovatelnost výsledků; kalibrace; Reproducibility of Results; elektrická vodivost; limita detekce; Acids; Spectrophotometry, Ultraviolet; lidé; Humans; Limit of Detection; Electrophoresis, Capillary; Calibration; spektrofotometrie ultrafialová